IMPROVING STUDENT’S READING SKILLS THROUGH RECOUNT TEXT AT 10TH GRADE OF SMK SMART BEKASI - Dwi Julian Nurrahim (Jurnal Web Informatika Teknologi, 2022)
This study is called Classroom Action Research (CAR), and it tries to answer students' difficulties in class. During the learning process, it was discovered that most students struggled to learn English owing to a lack of expertise in reading comprehension, as well as a lack of vocabulary knowledge. According to the exam findings, the average student score is still quite low, 64.3, and does not satisfy the required KKM level. The purpose of this study is to improve reading comprehension and raise students' learning motivation, particularly in reading activities. The researcher picked the cue picture as a learning method because students at the vocational high school level were more engaged in the usage of pictures, thus the researcher utilized cue pictures as a learning approach in increasing reading comprehension abilities. This study has two cycles. There were two meetings in the first cycle and four meetings in the second cycle. Students are given a different reading material and questions at each meeting. The subjects of this study were 25 SMK Smart Bekasi class X students. Observation lists, daily notebooks, and achievement assessments were used to collect data. The study determined that the cue picture method was successful if two conditions were satisfied. (1) 87.5% of pupils achieved a score of 75, and (2) 80% participated actively in the learning process. After the researcher used the technique, the pupils' average score increased to 84. The study discovered that 90.14% of the 25 students actively participated in the learning process